2013
DOI: 10.1186/1471-2180-13-95
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage environment turns otherwise MccJ25-resistant Salmonella into sensitive

Abstract: BackgroundMicrocin J25 (MccJ25) is a plasmid-encoded antibiotic peptide produced by Escherichia coli (E. coli). MccJ25 enters into the sensitive E. coli strains by the outer membrane receptor FhuA and the inner membrane proteins TonB, ExbB, ExbD and SbmA. The resistance of Salmonella enterica serovar Typhimurium (S. Typhimurium) to MccJ25 is attributed to the inability of its FhuA protein to incorporate the antibiotic into the cell.ResultsIn this work we demonstrate that S. Typhimurium becomes notably suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A mildly acidic pH was previously proposed to play a role based on an in vivo synergistic effect of the DNA gyrase inhibitor novobiocin and acidic pH on DNA relaxation [ 50 ]. However, this observation can be explained by a mildly acidic pH increasing permeability to novobiocin [ 51 ]. Changes in the abundance of putrescine and spermidine, or in a metabolite yet to be identified, may contribute to the reported decrease in global DNA supercoiling.…”
Section: Discussionsupporting
confidence: 55%
“…A mildly acidic pH was previously proposed to play a role based on an in vivo synergistic effect of the DNA gyrase inhibitor novobiocin and acidic pH on DNA relaxation [ 50 ]. However, this observation can be explained by a mildly acidic pH increasing permeability to novobiocin [ 51 ]. Changes in the abundance of putrescine and spermidine, or in a metabolite yet to be identified, may contribute to the reported decrease in global DNA supercoiling.…”
Section: Discussionsupporting
confidence: 55%
“…Novobiocin at 10 μg ml −1 resulted in greater DNA relaxation at pH 4 than at pH 7. This was consistent with the known ability of acid treatment to enhance the uptake of novobiocin by the bacterium (Ofek et al ., ; Pomares et al ., ; see Discussion ).…”
Section: Resultsmentioning
confidence: 73%
“…In considering our results, we took into account previous data showing that growth at acid pH enhances novobiocin uptake by Salmonella (Ofek et al ., ; Pomares et al ., ). In a pH 7 culture, the effect of 10 μg ml −1 novobiocin was similar to the degree of relaxation seen due to acid treatment alone in the drug‐free pH 4 culture (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…There are some data on the characterization of outer membrane proteins of M. haemolytica [ 36 , 37 ] but we don’t know whether specific membrane proteins exist to facilitate transport of MccJ25. Furthermore, MccJ25 is not effective against many bacteria of the family Enterobacteriaceae that are not related to the MccJ25 producing members [ 38 ]. It could be argued that MccJ25 shows a narrow action spectrum activity in vitro but could be active in vivo against resistant species [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MccJ25 is not effective against many bacteria of the family Enterobacteriaceae that are not related to the MccJ25 producing members [ 38 ]. It could be argued that MccJ25 shows a narrow action spectrum activity in vitro but could be active in vivo against resistant species [ 38 , 39 ]. It has been shown that resistant bacteria become susceptible to antibiotics upon their entry into the low pH environment in the phagolysosomes of macrophages likely due to the nonspecific MccJ25 uptake into the bacterial cell through altered bacterial membrane permeability.…”
Section: Discussionmentioning
confidence: 99%